360° size-adjustable microelectrode array system for electrophysiological monitoring of cerebral organoids - Ozaki, Takashi; Ohta, Norikazu; Ma, Jiaju; Hirano, Minoru (Frontiers in Bioengineering and Biotechnology, 2025)
This paper presents a 360°, size-adjustable microelectrode array (MEA) system for the long-term electrophysiological monitoring of cerebral organoids derived from human pluripotent stem cells. The system consists of eight independently positionable multielectrode probes, each carrying eight electrodes arranged vertically. This configuration resulted in 64 recording channels surrounding the organoid. The multielectrode probes were mounted on custom-designed miniature manipulators with three degrees of freedom. This setup enabled positioning and contact with organoids of varying sizes (approximately 1–3.7 mm in diameter). The design allowed circumferential access and facilitated standard incubator-based cultivation without disrupting the recording setup. Fabricated using flexible printed circuit technology, this MEA system offers relatively low production costs. It is also amenable to widespread implementation in laboratory settings. Experimental results demonstrated the successful recording of neuronal activity, including spike detection and signal stability, over 2 weeks of continuous organoid culture. These results suggests that the three-dimensional system provides broad spatial coverage and supports long-term monitoring for basic biomedical research. It also holds potential for future applications such as biohybrid computing.